Megoak-goakan game with vak model improves elementary students' mathematical concept understanding - Muhardila Fauziah; Malysa Harteva Putri; Niken Wahyu Utami; Azamul Fadhly Noor Muhammad; Ravinesh Rohit Prasad (Prodi PGSD FKIP Universitas Islam Sultan Agung, 2026)
This study investigated the effectiveness of a traditional megoak-goakan game, integrated with the Visual, Auditory, Kinesthetic (VAK) learning model and supplemented with student worksheets (LKS), in enhancing Phase A elementary school students' understanding of mathematical concepts. Using a quasi-experimental approach with a time-series design, the research was conducted with first-grade students at SDN Kranji VI and SDN Kayuringin Jaya VI in Bekasi City. The findings showed a significant improvement in students' understanding of mathematical concepts. Post-test scores and N-Gain scores increased by 35% at SDN Kranji VI and 51% at SDN Kayuringin Jaya VI. These results suggest that integrating traditional games with the VAK model and LKS provides an interactive and enjoyable learning experience, effectively improving mathematical concept understanding as well as students' social and emotional skills.